Protective Effect of Ethanolic Extract Tempuyung Leaf (Sonchus arvensis L.) in Gentamicin-induced Acute Tubular Necrosis on Wistar Rats - Imelda, Imelda -; Achadiyani, Achadiyani -; Sekarwana, Nanan - (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2018)
Acute tubular necrosis (ATN) is the most common histopathologic findings of acute kidney injury (AKI). AKI is marked by the decrement of glomerular filtration rate, causing waste metabolism retention (creatinine). Gentamicin is used as it is the most common nephrotoxic agent in inducing ATN. Tempuyung (Sonchus arvensis L.) has been used in folklore medicine to ameliorate kidney problems as it contains antioxidants, two of which are flavonoid and phenolic acid. Yet, these active substances’ benefit on gentamicin induced ATN has not been investigated in Indonesia. This research aims to analyze protective effect of ethanolic extract tempuyung leaf (EET) on gentamicin-induced ATN based on histopathological study and creatinine serum level. True experimental laboratoric study was done with simple random design on male wistar rats, randomly divided into 4 groups (n=4). Control group (CMC 0.5% aquadest); Induction group (Gentamicin 80 mg/kgBW); 1st treatment group (EET 100 mg/kgBW + Gentamicin 80 mg/kgBW) and 2nd treatment group (EET 200 mg/kgBW + Gentamicin 80 mg/kgBW) for ten days. On the 11th day, blood was taken for creatinine measurement and kidneys collection for histopathological study. Histopathological examination on gentamicin-treated rats revealed degenerative changes in kidney tubules. Aside from that, gentamicin-treated rats also showed increment in creatinine serum level. Conversely, simultaneous administration of EET with Gentamicin ameliorated the nephrotoxic effects of gentamicin as confirmed from the significant improvement on histopathological changes and normalization of creatinine serum level. Co-administration of EET and gentamicin provides protection on gentamicin-induced ATN, based on histopathological feature and creatinine serum level.